I'm having trouble figuring out how to correctly apply boundary conditions to the general solution of a PDE. I'm seeking a particular solution $u(x,t)$ for \begin{align} 4u_{x} + u_{t} &= 0 \qquad 0 < x < \infty \\ u(x,0) &= 0\qquad 0 < x <\infty \\ u(0,t)& = te^{-t} \qquad t>0 \end{align} Specifically, I'm not exactly sure how to handle the condition $u(x,0) = 0$. Here's my work:

In general, a solution to the PDE of the form $au_{x} + bu_{t} = 0$ is $u(x, t) = f(bx - at)$. For our PDE, $a=4$, $b=1$ and we have $u(x, t) = f(x - 4t)$.

For the initial condition $u(0, t) = f(-4t) = te^{-t}$. Let $w = -4t$. Then $f(-4t) = f(w) = -\frac{w}{4}e^{\frac{w}{4}}$ which implies that one particular solution of the PDE is \begin{equation} u(x, t) = f(x - 4t) = (t - \frac{x}{4})e^{\frac{x}{4} - t} \end{equation} Next, $u(x,0) = f(x) = 0 = -\frac{x}{4}e^{\frac{x}{4}}$. But this implies $x = 0$, forcing $u(x, t) = te^{-t}$, which clearly doesn't satisfy our original PDE.

Not sure where to go from here. The problem also stipulates that a solution to the equation $4u_{t} + u_{x}=0$ has no solution and asks us to explain why. I'm hoping I'll be able to answer that question once I figure out what I'm doing wrong here.

Any advice on how to correct my error(s) would be greatly appreciated!


Your calculus is correct.

The general solution is $u=f(x-4t)$

As you found it, the condition $u(0,t)=te^{-t}$ implies $u(x,t)=(t - \frac{x}{4})e^{\frac{x}{4} - t}$

If you do the same calculus with the condition $u(x,0)=0$, you obtain $f(x)=0$ which implies $u(x,t)=0$.

The two conditions are incompatible because they leads to two different solutions $u(x,y)$. As a consequence, there is no function $u(x,y)$ solution of the PDE which satisfy both two conditions : The problem has no solution.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.